2023
DOI: 10.1021/acs.inorgchem.3c01666
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Reconstruction of the Heterointerface Electronic Structure by the Enriched Oxygen Vacancy for the Oxygen Evolution Reaction

Abstract: Exploring high-performance non-precious metal-based electrocatalysts for the sluggish oxygen evolution reaction (OER) process is fundamentally significant for the development of multifarious renewable energy conversion and storage systems. Oxygen vacancy (Vo) engineering is an effective leverage to boost the intrinsic activity of OER, but the underlying catalytic mechanism remains anfractuous. Herein, we realize the construction of oxygen vacancy-enriched porous NiO/ln2O3 nanofibers (designated as Vo–NiO/ln2O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Abundant Vo modulated the electronic configuration of the catalyst for altering the adsorption of intermediates to reduce the OER overpotential and promote *O formation, upshifting the d band center of metal centers near the Fermi level, and also increasing the electrical conductivity and enhancing the OER reaction kinetics simultaneously. In situ Raman spectra suggested that the Vo can render the NiO/ln 2 O 3 more easily reconstructible on the surface during the OER course [201].…”
Section: Nioxmentioning
confidence: 99%
“…Abundant Vo modulated the electronic configuration of the catalyst for altering the adsorption of intermediates to reduce the OER overpotential and promote *O formation, upshifting the d band center of metal centers near the Fermi level, and also increasing the electrical conductivity and enhancing the OER reaction kinetics simultaneously. In situ Raman spectra suggested that the Vo can render the NiO/ln 2 O 3 more easily reconstructible on the surface during the OER course [201].…”
Section: Nioxmentioning
confidence: 99%
“…Abundant Vo modulated the electronic configuration of the catalyst for altering the adsorption of intermediates to reduce the OER overpotential and promote O* formation, upshifting the d band center of metal centers near the Fermi level, and also increasing the electrical conductivity and enhancing the OER reaction kinetics simultaneously. In situ Raman spectra suggested that the Vo can render the NiO/ln2O3 more easily reconstructible on the surface during the OER course [201].…”
Section: Mn Comentioning
confidence: 99%
“…1–3 Differentiation from existing hydrogen production approaches, the electrochemical hydrogen evolution reaction (HER), which can be powered by intermittent renewable electricity, is considered an effective and facile targeted approach for generating high-purity green hydrogen, and therefore has drawn considerable attention recently. 4–6 Compared with acidic and neutral solutions, the alkaline electrocatalytic HER is more attractive as it takes advantage of its lower corrosiveness to equipment and materials. In addition, the HER pathway in alkaline media works under an additional Volmer step (M + H 2 O + e − → M–H ads + OH − ) for water dissociation in advance of the Heyrovsky (M–H ads + H 2 O + e − → M + H 2 + OH − ) or Tafel (2M–H ads → 2M + H 2 ) step, which leads to the sluggish water adsorption/dissociation process during HER.…”
Section: Introductionmentioning
confidence: 99%